Prácticas Del Uso De La Botánica Tradicional Para La prevención Y Cuidado Cultural De La Enfermedad De Alzheimer En El Resguardo indígena La Gaitana Inzá Cauca - Silva Macías, Ángela Daniela; Chantre Perdomo, Endy Soraya; Meza Pérez, Marlenne Juliana (Universidad Antonio Nariño, 2022)
The purpose of this is to make use of the ancestral knowledge of the Nasa indigenous community, established in the municipality of Inzá Cauca, through the application of traditional botany, which seeks to contribute to the prevention and care of Alzheimer's disease, since it is considered a public health problem, due to to the high costs both at family and collective level. A descriptive qualitative study was carried out, which included performing of semi-structured interviews with participants who are part of the NASA community of the shelter the Gaitana Inzá Cauca called wala, allowing to identify the ancestral practices centered on their own culture and beliefs. Likewise, it was contrasted this type of experience in the light of Madeleine Leininger's theory, which is oriented in establishing an important place for cultural identities, allowing and guiding professionals in the field of health in the incorporation of new knowledge and practices to improve the quality and care of people's health. Seen in this way, it is important to know the different cultures that exist in the Colombian population and its contributions, both for the prevention and care of the disease of Alzheimer's and other existing pathologies, since each culture has a different management according to their ancestral knowledge that has been maintained through the years since the different practices that strengthen and that underlie to obtain preventive effects or with Curative purposes, in such a way that nursing can be enriched with new knowledge to provide care from a differential and comprehensive approach for the benefit of the population